2015
DOI: 10.1111/eea.12376
|View full text |Cite
|
Sign up to set email alerts
|

Industrial pollution affects behaviour of the leafmining moth Stigmella lapponica

Abstract: We explored the impacts of industrial air pollution on the behaviour of the leafmining moth Stigmella lapponica (Wocke) (Lepidoptera: Nepticulidae) by comparing the characteristics of larval gallery mines in mountain birch [Betula pubescens ssp. czerepanovii (Orlova) H€ amet-Ahti (Betulaceae)] leaves collected from unpolluted forests and from heavily polluted industrial barrens surrounding the copper-nickel smelter in Monchegorsk in north-western Russia. Population density of S. lapponica, survival of larvae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The samples were taken to the laboratory, where they were sorted by species (using an online identification guide: Ellis, ) and then classified as either undamaged empty mines left by larvae which successfully completed their development (i.e., survived individuals) or mines containing dead larvae or opened by predators (i.e., dead individuals). Earlier studies demonstrated that mine size decreases, distance between the turns of larval gallery increases and angle of turns decreases with an increase in quality of plant foliage as a food for leafminers (Kozlov & Zvereva, ; Low & Hanley, ; Low et al., ; Stiling et al., ). Therefore, to compare plant quality between habitats, we studied undamaged empty mines of Stigmella confusella and Stigmella lapponica .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were taken to the laboratory, where they were sorted by species (using an online identification guide: Ellis, ) and then classified as either undamaged empty mines left by larvae which successfully completed their development (i.e., survived individuals) or mines containing dead larvae or opened by predators (i.e., dead individuals). Earlier studies demonstrated that mine size decreases, distance between the turns of larval gallery increases and angle of turns decreases with an increase in quality of plant foliage as a food for leafminers (Kozlov & Zvereva, ; Low & Hanley, ; Low et al., ; Stiling et al., ). Therefore, to compare plant quality between habitats, we studied undamaged empty mines of Stigmella confusella and Stigmella lapponica .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, to compare plant quality between habitats, we studied undamaged empty mines of Stigmella confusella and Stigmella lapponica . Twenty‐five randomly selected mines of each species from each habitat were measured following the protocol described by Kozlov and Zvereva (). Each mine was approximated by a broken line made up of straight segments following the line of excrements as closely as possible (8–61 segments per mine).…”
Section: Methodsmentioning
confidence: 99%
“…The standard instruments of Adobe PhotoShop 2020 were used to measure the length of each segment (to the nearest 0.06 mm) and the angle between two adjacent segments (to the nearest 1°). The segment length and the angles of the turns of the mine (excluding those at the intersections with leaf veins) were averaged for each mine prior to analysis following the protocol developed by Kozlov and Zvereva (2016).…”
Section: Methodsmentioning
confidence: 99%
“…In northern Europe, mines of S. lapponica are equally frequent on B. pubescens and B. pendula, and the mine densities (per unit of host biomass) decrease toward the north (Kozlov et al, 2013). Females preferentially oviposit on the basal half of a leaf, but they relax this preference in areas affected by severe industrial pollution (Kozlov & Zvereva, 2016).…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation